First Estimates of Age and Growth of the Lusitanian Cownose Ray (Rhinoptera marginata) from the Mediterranean Sea - Basusta, Nuri; Basusta, Asiye; Cicek, Erdogan; Cicia, Angela M.; Sulikowski, James A. (Mdpi, 2022)
Within the eastern Mediterranean, increased fishing pressure coupled with a lack of basic biological information is threatening the sustainability of the rare Lusitanian cownose ray (Rhinoptera marginata). To provide baseline life-history data for this species, age estimates were obtained from vertebral band counts of 224 rays (size range: 210-998 mm disc width and 140 to 13,600 g weight) collected from Iskenderun Bay. Females ranged in size from 210 to 998 mm disc width and 238 to 13,600 g weight, while males ranged from 130 to 866 mm disc width and 140 to 8250 g weight. The index of average percent error (2.8%) and age-bias plot suggest that the aging method used represents a precise and non-biased approach. Marginal increment analysis indicated that a single opaque band is deposited annually between August and September. The oldest ages obtained for R. marginata were 9 years for males and 19 years for females, which corresponded to total lengths of 866 and 998 mm disc width, respectively. For males, limited samples prevented the accurate calculation of growth rates; however, for combined sexes, observed and disc width-at-age data resulted in the following von Bertalanffy growth parameters: DW infinity = 1102.16 mm, k = 0.148 and t(0) = -0.2167. Although additional samples are necessary to determine growth rates in males, the results of the present study indicate that R. marginata females exhibit life history characteristics similar to other Rhinoptera species.
Keywords: elasmobranch; Rhinopteridae; batoids; age; growth; Mediterranean